2021
DOI: 10.1016/j.yebeh.2021.108255
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic nonepileptic seizures during the COVID-19 pandemic in New York City – A distinct response from the epilepsy experience

Abstract: Although psychogenic nonepileptic seizures (PNES) are a common neurologic condition, there remains a paucity of literature on the COVID-19 pandemic’s effect on these patients. Using a cross-sectional questionnaire study, our group examined the experience of patients with PNES at a single Comprehensive Epilepsy Center in New York City, the epicenter of the initial COVID-19 outbreak in the United States. Among our cohort of 18 subjects with PNES, 22.2% reported an improvement in seizure control during the peak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In a survey of 54 patients with FS, 15 people (28%) reported increased frequency of FS during the pandemic in Brazil [22] . In contrast, in a survey of 18 people with FS, 22.2% reported an improvement in seizure control during the peak of the COVID-19 pandemic in New York City [23] . The nature of these studies (survey) and the risk of recall bias associated with their methodology may explain their contradictory results.…”
Section: Discussionmentioning
confidence: 85%
“…In a survey of 54 patients with FS, 15 people (28%) reported increased frequency of FS during the pandemic in Brazil [22] . In contrast, in a survey of 18 people with FS, 22.2% reported an improvement in seizure control during the peak of the COVID-19 pandemic in New York City [23] . The nature of these studies (survey) and the risk of recall bias associated with their methodology may explain their contradictory results.…”
Section: Discussionmentioning
confidence: 85%
“…According to a systematic review and meta-analysis, the proportion of abnormal EEG in C19 subjects is as high as 96% 16 . Non-specific, generalized background or diffuse slowing has been reported in several studies as the most common finding 10 , 11 , 18 , whereby EEG abnormalities correlate with encephalopathy, disease severity 8 , 9 , 17 , and risk for novel seizures 13 , including psychogenic non-epileptic seizures 5 . In particular, delta waves with absence of epileptic activity have been documented 12 , as well as alpha coma patterns suggestive of SARS-CoV-2 neurotropism for the brainstem ascending reticular system 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggested that SARS-CoV-2 could preferentially and directly target the frontal lobes 19 , with EEG abnormalities localized to frontal electrodes 8 , 12 , our results did not confirm these qualitative observations. The mechanisms underlying these observations are largely unknown; however, it has been suggested that metabolic hypoxia 18 , immune-mediated neuro-inflammation 3 , as well as severe stress and sleep disturbances 5 , are likely contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three previous studies, it was observed that the COVID-19 pandemic may have associations with some of the characteristics of FS at diagnosis [6] , [7] , [8] . However, in FS, often there is a significant delay between the onset of functional seizures and the diagnosis of the condition.…”
Section: Introductionmentioning
confidence: 97%